2011
DOI: 10.1002/pssa.201127263
|View full text |Cite
|
Sign up to set email alerts
|

The properties of sol–gel processed indium‐doped zinc oxide semiconductor film and its application in organic solar cells

Abstract: Indium‐doped ZnO (IZO) films with various indium contents were deposited by sol–gel process for application in organic solar cells (OSCs). X‐ray photoelectron spectroscopy (XPS) spectrum verified that indium is incorporated in the ZnO films. All films showed polycrystalline nature with a hexagonal wurtzite structure of ZnO. The resistivity of the films initially decreases yet increases again with higher doping. The lowest resistivity of 5.54 × 10−1 Ω‐cm was obtained at 1 at.% indium‐doped film. The optical tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Another important feature of ZnO is controllable electrical, optical, and magnetic performance by doping with small amount of elements. It was reported that doping ZnO with a little amount of group III elements, such as gallium, aluminum, and indium could significantly enhance conductivity. Also, many studies reported the observation of above‐room‐temperature ferromagnetism from transition‐metal‐doped ZnO .…”
Section: Introductionmentioning
confidence: 99%
“…Another important feature of ZnO is controllable electrical, optical, and magnetic performance by doping with small amount of elements. It was reported that doping ZnO with a little amount of group III elements, such as gallium, aluminum, and indium could significantly enhance conductivity. Also, many studies reported the observation of above‐room‐temperature ferromagnetism from transition‐metal‐doped ZnO .…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide is an n-type material having a wide band gap (3.3 eV) [39]. Zinc oxide becomes n type due to intrinsic defects of oxygen vacancy and the interstices occupied by excessive zinc [39].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide becomes n type due to intrinsic defects of oxygen vacancy and the interstices occupied by excessive zinc [39]. The heat treatment atmosphere and temperature influence the thin film conductivity [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Transparent conducting oxides (TCO's) in thin films have become very important for a variety of applications including gas sensors (Ferro et al 2008), optoelectronic devices (Shinde et al 2008), organic solar cells (Kyaw et al 2011) and others. Zinc oxide (ZnO) thin films present a particular importance due to their great optical transmittance in the visible wavelength range.…”
Section: Introductionmentioning
confidence: 99%